Sistem Informasi Geografis Pemetaan Penyebaran Penyakit Berbasis Web Di Pekalongan - Tri Wahyu Utami (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2023)
Indonesia is a country consisting of many islands and isolated areas that have not been reached. These isolated areas have not been supported by health facilities. Therefore, the prevention of disease in the area is difficult to be solved. These problems can lead to the spread of the disease becomes wider and it can increase the number of deaths and physical disabilities. The presence of a web-based geographic information systems is able to help in overcoming the spread of the disease in a particular area. The geographic information systems can be applied to mark an area in determining the points of the transmission. Using the current health facilities, the data can be performed on the information systems and to find the areas that do not have proper health facilities. Geographic information system is produce the spread of diseases that determine how the diseases spread and help the areas that do not have health facilities to receive medical countermeasures from the parties concerned. It can give welfare to people who need help to have a proper health.